What are the key attributes of effective online teachers? - Sister Mary Rose O.P. (Angela Lavin) (Flexible Learning Association of New Zealand, 2018)
This article explores the key attributes of effective online tertiary educators. Using qualitative research methods, data were collected via semi-structured interviews which were conducted with a small group of university academics in New Zealand and Australia and analysed using an inductive approach and open and closed coding techniques. Results from the analysis identified the following five key attributes: effective online teachers avoid a didactic approach, vary their pedagogy, use productive failure, facilitate the learning process and provide a seamless structure. Given the limitations of the study, the findings cannot be generalised without further work, but do provide a roadmap which may support innovative adaptions to the teaching and learning process in an online space.